2008
DOI: 10.1080/09540260701878082
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of HIV related central nervous system disease

Abstract: In this review we critically assess biomarkers of the direct effects of HIV related brain disease. This area is becoming increasingly complex because of the presence of confounds and varying degrees of activity of HIV brain disease. Sensitive and specific biomarkers are urgently needed although existing biomarkers do have some utility. The review will focus on the practical implications of the more established biomarkers. We discuss blood, cerebrospinal fluid and neurophysiological biomarkers but not neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 137 publications
(145 reference statements)
0
26
1
Order By: Relevance
“…38 Both studies suggested that immune activation may actually provide a neuroprotective effect in the pediatric population. This is in stark contrast to the data in the adult population that shows deleterious effects of immune activation on the CNS 3941 . Both pediatric studies evaluated relatively young children (median age 6–7 years) with perinatal HIV who had only been on cART for a relatively short period of time or who were not on therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…38 Both studies suggested that immune activation may actually provide a neuroprotective effect in the pediatric population. This is in stark contrast to the data in the adult population that shows deleterious effects of immune activation on the CNS 3941 . Both pediatric studies evaluated relatively young children (median age 6–7 years) with perinatal HIV who had only been on cART for a relatively short period of time or who were not on therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…While no biomarker as of yet has proven to be clinically useful at predicting or diagnosing HIV-associated neurological disease, CSF levels of QUIN, MCP-1, and IL-6 are frequently cited as top biomarker candidates (Brew and Letendre 2008). QUIN in particular has been shown to differentiate between HIV-infected individuals with or without dementia (Heyes et al 1991), with or without functional impairments in motor-skill learning and reaction time (Martin et al 1993), as well as SIV-infected macaques with or without encephalitis (Heyes et al 1992a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIV transmission and incident infections are increasing among older adults, who in turn have a greater risk to develop cognitive impairment. 1,2 The Centers for Disease Control (CDC; Atlanta, GA) estimates that by 2015, half of all people living with HIV infection in the United States will be 50 years of age or older (www.cdc.gov/hiv/topics/over50) and in many localities this threshold has already been exceeded. Therefore, there is an urgent clinical need to better delineate neurologic complications and treatment in HIV+ individuals who are living longer, including those with sustained virologic suppression and immune reconstitution on cART.…”
Section: Aging With Hiv: a Rapidly Growing Populationmentioning
confidence: 99%